Population pharmacokinetics of ivermectin after mass drug administration in lymphatic filariasis endemic communities of Tanzania - Adam M. Fimbo; Eulambius M. Mlugu; Eliford Ngaimisi Kitabi; Gerald S. Kulwa; Mohammed A. Iwodyah; Rajabu Hussein Mnkugwe; Peter P. Kunambi; Alpha Malishee; Appolinary A. R. Kamuhabwa; Omary M. Minzi; Eleni Aklillu (Wiley, 2023)
Abstract Ivermectin (IVM) is a drug of choice used with albendazole for mass drug administration (MDA) to halt transmission of lymphatic filariasis. We investigated IVM pharmacokinetic (PK) variability for its dose optimization during MDA. PK samples were collected at 0, 2, 4, and 6 h from individuals weighing greater than 15 kg (n = 468) receiving IVM (3‐, 6‐, 9‐, or 12 mg) and ALB (400 mg) during an MDA campaign in Tanzania. Individual characteristics, including demographics, laboratory/clinical parameters, and pharmacogenetic variations were assessed. IVM plasma concentrations were quantified by liquid‐chromatography tandem mass spectrometry and analyzed using population‐(PopPK) modeling. A two‐compartment model with transit absorption kinetics, and allometrically scaled oral clearance (CL/F) and central volume (Vc/F) was adapted. Fitting of the model to the data identified 48% higher bioavailability for the 3 mg dose compared to higher doses and identified a subpopulation with 97% higher mean transit time (MTT). The final estimates for CL/F, Vc/F, intercompartment clearance, peripheral volume, MTT, and absorption rate constant for a 70 kg person (on dose other than 3 mg) were 7.7 L/h, 147 L, 20.4 L/h, 207 L, 1.5 h, and 0.71/h, respectively. Monte‐Carlo simulations indicated that weight‐based dosing provides comparable exposure across weight bands, but height‐based dosing with capping IVM dose at 12 mg for individuals with height greater than 160 cm underdoses those weighing greater than 70 kg. Variability in IVM PKs is partly explained by body weight and dose. The established PopPK model can be used for IVM dose optimization. Height‐based pole dosing results in varying IVM exposure in different weight bands, hence using weighing scales for IVM dosing during MDA is recommended.